Zero phase sequence voltage injection for the alternate arm converter - Moreno,FJ; Merlin,MMC; Trainer,DR; Green,TC; Dyke,KJ (IET, 2015)
The Alternate Arm Converter (AAC) is a voltage source converter being developed as an alternative to the Modular Multilevel Converter (MMC) for HVDC power transmission and reactive power compensation. Each Arm of the converter contains high voltage series IGBT Director Switches and full-bridge cells, which enables the VSC to ride through AC and DC network faults. This paper describes how the AAC can be optimised by modulating the converter terminal voltages with zerophase sequence triplen harmonic components. The optimisation reduces the ratio of the number of the full-bridge cells compared to the simpler Director Switches which offers a valuable improvement in footprint and efficiency.